2021
DOI: 10.1002/ddr.21868
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin inhibits autophagy and epithelial‐mesenchymal transition of human lens epithelial cells by regulating the Smad2/3 pathway

Abstract: Cataract is the number one cause of blindness in the world. Fibrosis of the lens is the main cause of cataract. Pathological epithelial‐mesenchymal transition (EMT) plays an important role in the development of fibrotic cataract. Inhibition of EMT may be an effective treatment for fibrosis of lens epithelial cells. Naringin (NRG) is one of the major citrus flavonoids, which has many pharmacological properties, including anti‐inflammatory and cardioprotective. However, the effect of NRG on cataract induced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…All the compounds that might participate in the regulatory processes of JPYSF in EMT were considered as potential active ingredients. In support of this, several previous studies have shown that quercetin ( Elumalai et al, 2021 ), kaempferol ( Ji et al, 2020 ), luteolin ( Cao et al, 2020 ), naringenin ( Li et al, 2021 ), isorhamnetin, Tanshinone IIA ( Fu et al, 2021 ), cryptotanshinone ( Zhang Z et al, 2020 ), and aloe-emodin ( Liu et al, 2021 ) had well-established roles in EMT . Taken together, our results demonstrate that the core components may be the effective ingredients of JPYSF for the EMT treatment.…”
Section: Discussionmentioning
confidence: 59%
“…All the compounds that might participate in the regulatory processes of JPYSF in EMT were considered as potential active ingredients. In support of this, several previous studies have shown that quercetin ( Elumalai et al, 2021 ), kaempferol ( Ji et al, 2020 ), luteolin ( Cao et al, 2020 ), naringenin ( Li et al, 2021 ), isorhamnetin, Tanshinone IIA ( Fu et al, 2021 ), cryptotanshinone ( Zhang Z et al, 2020 ), and aloe-emodin ( Liu et al, 2021 ) had well-established roles in EMT . Taken together, our results demonstrate that the core components may be the effective ingredients of JPYSF for the EMT treatment.…”
Section: Discussionmentioning
confidence: 59%
“…Increased E-cadherin and decreased MMP-9 expression were observed in the present study following MSpf treatment. In addition, recent studies have suggested that autophagy and EMT are associated with regulation of tumorigenesis and tumor progression ( 46 , 47 ). Taken together, these results suggested that MSpf treatment regulated induction of autophagy and suppression of EMT in DLD-1 cells and that MSpf treatment may be a valuable therapeutic strategy for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a major process that contributes to the maintenance of intracellular energy metabolism and self‐survival 18 . Recently, it has been demonstrated that autophagy and EMT are tightly correlated in regulating tumorigenesis and tumour progression 19,20 . During the initial stage of tumour, autophagy suppresses cancer invasion and metastasis by selectively degrading important signalling molecules in the EMT process 19 .…”
Section: Discussionmentioning
confidence: 99%
“…18 Recently, it has been demonstrated that autophagy and EMT are tightly correlated in regulating tumorigenesis and tumour progression. 19,20 During the initial stage of tumour, autophagy suppresses cancer invasion and metastasis by selectively degrading important signalling molecules in the EMT process. 19 In contrast, during the process of tumour metastasis and diffusion, cancer cells need to activate autophagy to obtain sufficient energy and promote EMT.…”
Section: Discussionmentioning
confidence: 99%